2021
DOI: 10.1002/ana.26062
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis Is Rare in Epstein–Barr Virus–Seronegative Children with Central Nervous System Inflammatory Demyelination

Abstract: Although Epstein–Barr virus (EBV) is hypothesized to be a prerequisite for multiple sclerosis (MS), up to 15% of children with a diagnosis of MS were reported to be EBV‐seronegative. When re‐evaluating 25 EBV‐seronegative children out of 189 pediatric patients with a diagnosis of clinically isolated syndrome/MS, we found anti–myelin oligodendrocyte glycoprotein (MOG) antibody in 11 of 25 (44%) EBV‐seronegative but only 9 of 164 (5.5%, p < 0.001) EBV‐seropositive patients. After critical review, MS remained a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
(35 reference statements)
1
9
1
Order By: Relevance
“…These features were significant in univariate analysis and remained significant in multivariate analysis. These results are similar to those of prior studies, 35 including a recent study that found that EBV seronegativity in children with an MS‐like presentation may suggest an alternate diagnosis, particularly MOGAD 36 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These features were significant in univariate analysis and remained significant in multivariate analysis. These results are similar to those of prior studies, 35 including a recent study that found that EBV seronegativity in children with an MS‐like presentation may suggest an alternate diagnosis, particularly MOGAD 36 …”
Section: Discussionsupporting
confidence: 91%
“…These results are similar to those of prior studies, 35 including a recent study that found that EBV seronegativity in children with an MS-like presentation may suggest an alternate diagnosis, particularly MOGAD. 36 Additional features that may suggest a MOGAD diagnosis over MS include: lack of new MRI T2 brain lesions around the 12-month timepoint and resolution of most or all T2-lesions with follow-up (Fig ), as shown in recent studies, 37,38 as well as female sex (significant in the multivariable model only), initial optic nerve localization (significant in the univariable model only), and lack of CSF OCBs and initial spinal cord localization (both significant in the univariable model only). Although MOGAD cases were less likely to have CSF OCBs, OCBs were present in one-fifth of these patients; therefore, the presence of CSF OCBs should not exclude a MOGAD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…While our research protocol did not direct the timing or selection of DMTs, we did not feel that therapy affected our ability to identify the atypical clinical features of MOG-IgG positive patients, as 9/12 never received DMT. Other features, such as serology evidence of prior Epstein–Barr virus (EBV) infection, 35 could contribute in differentiating pediatric MS from MOGAD, 36 and should be object of future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, EBV infection alone is not sufficient to cause the disease and other factors such as genetic traits may contribute substantially to EBV-associated MS risk. As a lower frequency of EBV seropositivity has been reported in POMS, 11,[13][14][15] it makes this age group ideal for assessing genetic susceptibility to EBV-associated MS.…”
Section: Gene-environment Interactions: Epstein-barr Virus Infection ...mentioning
confidence: 99%